2003
DOI: 10.1089/107632703762687636
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Regeneration of Periodontal Tissues Based onin SituTissue Engineering: Effects of Controlled Release of Basic Fibroblast Growth Factor from a Sandwich Membrane

Abstract: To regenerate periodontal tissues, a sandwich membrane composed of a collagen sponge scaffold and gelatin microspheres containing basic fibroblast growth factor (bFGF) in a controlled-release system was developed according to the new concept of "in situ tissue engineering." A three-walled alveolar bone defect (3 x 4 x 4 mm) was made bilaterally in edentulous regions created mesially to the canines in both the maxilla and mandible of nine beagle dogs. A sandwich membrane with or without bFGF (100 microg) was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 27 publications
2
67
0
Order By: Relevance
“…35 Application of FGF2 to periodontal tissue regeneration has been previously reported. 36,37 FGF2 can be immobilized on to Ti surface 24 and hydroxyapatite-chitosan scaffolds. 38 The immobilization procedure used in this study as well as the chemical inertness and stability of TiO 2 ensure that there is very little possibility for the FGF2 to react with the TiO 2 NT array.…”
Section: Discussionmentioning
confidence: 99%
“…35 Application of FGF2 to periodontal tissue regeneration has been previously reported. 36,37 FGF2 can be immobilized on to Ti surface 24 and hydroxyapatite-chitosan scaffolds. 38 The immobilization procedure used in this study as well as the chemical inertness and stability of TiO 2 ensure that there is very little possibility for the FGF2 to react with the TiO 2 NT array.…”
Section: Discussionmentioning
confidence: 99%
“…The basic components for tissue engineering involve an interactive triad of scaffolds [79][80][81] , signaling molecules [82][83][84] and cells [24,33,41,85] , which play a fundamental role in the regeneration process [24,76,86,87] . Scaffolds serve as a threedimensional template mimicking the extracellular matrix; signaling molecules enhance this cellular activity by stimulating cells to migrate, proliferate and differentiate; and cells provide the machinery synthesis of the extracellular matrix and tissue regeneration [24,75,76,88,89] .…”
Section: Perspectives On Tdscs In Regenerative Approachesmentioning
confidence: 99%
“…In preclinical studies, this growth factor was evaluated for the treatment of different types of periodontal bone defects, in dogs [92][93][94][95] and non-human primates [96]. Despite different concentrations of FGF-2 and different delivery systems used in the studies, all showed an improvement in the periodontal tissue regeneration, compared with control groups.…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%